1987
DOI: 10.1095/biolreprod37.1.82
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Histological and Non-histological Indices of Atresia and Follicular Function1

Abstract: Histological indices of atresia for bovine follicles greater than or equal to 5 mm in diameter were compared with potential non-histological indices of atresia such as opaqueness of the exposed surface of non-excised follicles, concentrations of steroids in follicular fluid (FF) and specific binding of gonadotropins by granulosal cells. Each non-excised follicle was classified as clear (n=86), intermediate (n=79), or opaque (n=115), on the basis of the appearance of its exposed surface. A section of tissue fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
39
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 0 publications
7
39
1
Order By: Relevance
“…Considering bovine follicles !5 mm only, the elevated levels of progesterone in follicular fluid indicate basal atresia (Irving-Rodgers et al 2003b) and this was also observed in an earlier study of bovine follicles O5 mm diameter, which were classified histologically as either healthy or atretic (Grimes et al 1987). In that study, w6% of the follicles were classified as 'atreticluteinized' and described as having elongated and hypertrophied granulosa cells and a disorganized theca.…”
Section: Atresia Of Antral Follicles !5 MM In Diametersupporting
confidence: 63%
See 1 more Smart Citation
“…Considering bovine follicles !5 mm only, the elevated levels of progesterone in follicular fluid indicate basal atresia (Irving-Rodgers et al 2003b) and this was also observed in an earlier study of bovine follicles O5 mm diameter, which were classified histologically as either healthy or atretic (Grimes et al 1987). In that study, w6% of the follicles were classified as 'atreticluteinized' and described as having elongated and hypertrophied granulosa cells and a disorganized theca.…”
Section: Atresia Of Antral Follicles !5 MM In Diametersupporting
confidence: 63%
“…Numerous studies of bovine follicles have measured steroid hormone concentrations in follicular fluids with different indicators of atresia or cell death used to determine whether the steroid concentrations are indeed good measures of atresia (Ireland & Roche 1983, McNatty et al 1984, Grimes et al 1987, Jolly et al 1994). The consensus is that healthy follicles have higher levels of E 2 than atretic follicles, and atretic follicles have higher levels of progesterone or thecal products such as testosterone or androstenedione for the same size of follicle.…”
Section: Atresia Of Antral Follicles O5 MM In Diametermentioning
confidence: 99%
“…Increased inhibin levels were noted that follicular fluid E2 levels in stage I to III follicles, which are classified as healthy growing follicles, are higher than those in atretic follicles (stages IV to VII), and that follicular fluid inhibin levels are related to E2 level but not P or T levels. High P level in follicular fluid was seen in luteinizing follicles [33], and we found the highest P level in follicular fluid of stage VII follicles (advanced stage of atresia). Thus, stage VII follicles were considered to be luteinizing follicles based on both histological and endocrinological findings.…”
Section: Changes In Inhibin Estradiol-17β Progesterone and Testostesupporting
confidence: 53%
“…Some investigators (Byskov, 1974, Sadrkhanloo et al, 1987and Huges and Gorospe, 1991 maintain that atresia can occur at any stage of development, suggesting that those follicles which ultimately ovulate have escaped atresia many times during the course of development. Others maintain that the phenomenon of atresia is limited to a particular stage of development (Grimes et al, 1987 andHirshfield, 1988), and that there is a single period of vulnerability during the development of antral follicles. Quantitative data pertinent to this is scarce.…”
Section: Introductionmentioning
confidence: 99%